Peran Audit Siklus Ekuitas dalam Mencegah Manipulasi Laporan Keuangan pada Era Transformasi Digital Perusahaan - Sari Rahayu; Muhammad Anugrah; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the role of equity cycle auditing in preventing financial statement manipulation amid corporate digital transformation. The increasing adoption of digital accounting systems and integrated financial technologies has enhanced efficiency while simultaneously introducing new risks related to data manipulation, system vulnerabilities, and governance challenges. Equity accounts represent owners’ interests and are therefore highly sensitive to misstatements, making effective auditing essential for ensuring financial reliability. This research adopts a descriptive qualitative approach by analyzing relevant literature, regulatory reports, and prior empirical studies to explore how equity cycle audits contribute to transparency, risk control, and fraud prevention. The findings indicate that equity cycle auditing strengthens financial statement reliability through substantive testing of equity transactions, evaluation of digital internal controls, and the use of audit technologies such as data analytics. Furthermore, effective equity audits support corporate governance by reducing moral hazard and reinforcing stakeholder trust. Despite challenges arising from technological complexity and human resource limitations, strategic audit strengthening, regulatory support, and continuous auditor competency development remain crucial to sustaining credible financial reporting in the digital era.